SEASONAL VARIATION IN COCOON SIZE IN POLY VOLTINE x BIVOLTINE HYBRIDS OF THE MULBERRY SILKWORM, BOMBYX MORI L. - SINGH, RAVINDRA; CHOUDHARY, NAZIA; DAS, RANUMA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Thirty six F, hybrids involving six poly voltine namely, BL, BLs. 96A, 96E, PM and 96H and six bivoltine breeds viz. CSR, CSR, CSR, CSR. CSR, and NBD, of the silkworm, Bombyx mori L, were evaluated for cocoon size variability during pre-monsoon (March- April, 2008), monsoon (August-September 2008) and post-monsoon (December- January. 2008-09). Results indicated great deal of variation in cocoon size in different hybrids in different seasons. Four poly Voltine x bivoltine hybrids namely, BL, X CSR BLos X CSR 7. BLos X CSR, and 96AX CSR were found to possess uniform cocoons in all the three seasons on the basis of standard deviation. The short listed hybrids can be exploited commercially to increase quality silk production.